Revitalisasi Pengelolaan Wakaf di Kota Langsa Perspektif Undang-Undang Wakaf - J. Junaidi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article discusses the problems of managing waqf assets in Aceh. Until now,  waqf management is still traditional regarding fiqh books, even though Indonesia has issued special regulations on waqf management. The purpose of this research is to analyze the management of waqf in Langsa City. This research is empirical legal research with a normative sociological approach. This article argues that waqf management is still traditional due to the understanding of the community and the Nazir think that waqf is only in the form of land and intended for worship facilities only. In addition, there is still a tug of war in the management of waqf assets between indigenous peoples and the government. Revitalization needs so that waqf assets can managed properly and correctly. The direction of revitalizations is; First, it relates to waqf regulation; second, nazir; third, the waqf paradigm (waqf culture); fourth,l waqf institution.